The Functional Independence of Skinner's Verbal Operants: Conceptual and Applied Implications†. (13th October 2016) - Fryling, Mitch J.
Abstract : Much has been said about B. F. Skinner's analysis of verbal behavior. This commentary specifically focuses on the functional independence of B. F. Skinner's verbal operants. While researchers have long been interested in this topic, the research literature on this topic has produced mixed results; it has shown that the verbal operants may be both functionally independent and functionally interdependent. This commentary considers the conceptual and applied implications of these mixed findings. The distinction between constructs and events is highlighted, with specific attention to how this distinction relates to the consideration of the verbal operants in behavior analysis. The value of further research on the functional independence of the verbal operants is considered, as well as the type of research studies that might be useful toward developing interventions for individuals with language delays. Copyright © 2016 John Wiley & Sons, Ltd.